Tecumseh, Shawnee County - Weber, Gregory (Kansas State University, The Chapman Center for Rural Studies, 2011)
The community of Tecumseh is located in Shawnee County, Kansas on the fringes of the state capital, Topeka. In the mid 1850s, proslavery settlers from Missouri founded the town. The first post office was established on March 3, 1855. Because of Tecumseh’s close location to Topeka, and the politics of its founders, it was involved in much of the chaos that enveloped Kansas during its bloody territorial years.
Gregory Weber, “Tecumseh, Shawnee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/58.
Keywords: E.L. Partridge; John Brown; Pottawatomie Massacre; Shawnee County; Tecumseh; Topeka